A jellyfish diet for the herbivorous green turtle Chelonia mydas in the temperate SW Atlantic - González Carman, Victoria (2014)
Feeding ecology of juvenile green turtles (Chelonia mydas) was studied from 2008 to 2011 at Samborombón Bay (35°30′–36°30′S, Argentina), combining data on digestive tract examination and stable isotope analysis through a Bayesian mixing model. We found that animal matter, in particular gelatinous plankton, was consumed in large proportions compared to herbivorous food items such as terrestrial plants and macroalgae. This diet is facilitated by the high abundance of gelatinous plankton in the region, thus confirming the adaptive foraging behaviour of the juveniles according to prey abundance in the SW Atlantic. To our knowledge, this is the first study to employ this combination of techniques and to conclusively demonstrate that animal matter, in particular gelatinous plankton, is important in the diet of the neritic green sea turtles.